1985
DOI: 10.1002/jnr.490130117
|View full text |Cite
|
Sign up to set email alerts
|

Response of nerve growth cone to focal electric currents

Abstract: Monopolar electric current pulses were focally applied through a micropipette to the growth cone of Xenopus embryonic neurons in culture. Application of the current directly in front of the growth cone modulated the rate of growth cone extension: Negative (sink) currents increased the growth rate, while positive (source) currents reduced the growth rate. When the currents were applied in a direction perpendicular to the direction of the neurite growth, both negative and positive currents produced inhibitory ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1985
1985
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(5 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Moreover, this growth is consistently oriented to the cathode. Patel et al [1985] applied electric pulses (pA/ J.LV) focally near growth cones of Xenopus neurons and noted directional growth toward the negative (sink) electrode. Both steady and pulsatile fields have been found to be effective in promoting directed neurite outgrowth despite the endogenous occurrence of pulsatile fields.…”
Section: Influence Of Electric Fields On Nerve Regenerationmentioning
confidence: 99%
“…Moreover, this growth is consistently oriented to the cathode. Patel et al [1985] applied electric pulses (pA/ J.LV) focally near growth cones of Xenopus neurons and noted directional growth toward the negative (sink) electrode. Both steady and pulsatile fields have been found to be effective in promoting directed neurite outgrowth despite the endogenous occurrence of pulsatile fields.…”
Section: Influence Of Electric Fields On Nerve Regenerationmentioning
confidence: 99%
“…Three types of extracellular cues have long been considered likely candidates for controlling neurite growth: (i) physical guidance (6,11,12), (ii) spatial/temporal gradients of diffusible (13)(14)(15)(16)(17) or bound (17-23) neurite growthpromoting molecules, and (iii) electric fields (24)(25)(26)(27). The possibility has been raised that neurotransmitters also might play a role (28), as it has been reported that certain cultured neurons isolated from the snail Helisoma stop neurite regeneration in response to serotonin or dopamine (29)(30)(31).…”
mentioning
confidence: 99%
“…Growth cones provide sites for new membrane addition (1, 9, 10) needed in neurite elongation, and they control the direction and extent of elongation (2, 3) through processes still poorly understood. Ultimately, growth cones become quiescent and disappear as final patterns of arborization are achieved.Three types of extracellular cues have long been considered likely candidates for controlling neurite growth: (i) physical guidance (6,11,12), (ii) spatial/temporal gradients of diffusible (13-17) or bound (17-23) neurite growthpromoting molecules, and (iii) electric fields (24)(25)(26)(27). The possibility has been raised that neurotransmitters also might play a role (28), as it has been reported that certain cultured neurons isolated from the snail Helisoma stop neurite regeneration in response to serotonin or dopamine (29-31).…”
mentioning
confidence: 99%
“…Three types of extracellular cues have long been considered likely candidates for controlling neurite growth: (i) physical guidance (6,11,12), (ii) spatial/temporal gradients of diffusible (13)(14)(15)(16)(17) or bound (17-23) neurite growthpromoting molecules, and (iii) electric fields (24)(25)(26)(27). The possibility has been raised that neurotransmitters also might play a role (28), as it has been reported that certain cultured neurons isolated from the snail Helisoma stop neurite regeneration in response to serotonin or dopamine (29)(30)(31).…”
mentioning
confidence: 99%